Antitumoral efficacy of the protease inhibitor gabexate mesilate in colon cancer cells harbouring KRAS, BRAF and PIK3CA mutations. - Giovanni Brandi; Simona Tavolari; Francesco De Rosa; Stefania Di Girolamo; Valentina Agostini; Maria Aurelia Barbera; Giorgio Frega; Guido Biasco (PLoS ONE, 2012)
The employment of anti-epidermal growth factor receptor (EGFR) antibodies represents a backbone of the therapeutic options for the treatment of metastatic colorectal cancer (mCRC). However, this therapy is poorly effective or ineffective in unselected patients. Mutations in KRAS, BRAF and PIK3CA genes have recently emerged as the best predictive factors of low/absent response to EGFR-targeted therapy. Due to the need for efficacious treatment options for mCRC patients bearing these mutations, in this short report we examined the antitumoral activity of the protease inhibitor gabexate mesilate, alone and in combination with the anti-EGFR monoclonal antibody cetuximab, in a panel of human CRC cell lines harbouring a different expression pattern of wild-type/mutated KRAS, BRAF and PIK3CA genes. Results obtained showed that gabexate mesilate significantly inhibited the growth, invasive potential and tumour-induced angiogenesis in all the CRC cells employed in this study (including those ones harbouring dual KRAS/PIK3CA or BRAF/PIK3CA mutation), while cetuximab affected these parameters only in CRC cells with KRAS, BRAF and PIK3CA wild-type. Notably, the antitumoral efficacy of gabexate mesilate and cetuximab in combination was found to be not superior than that observed with gabexate mesilate as single agent. Overall, these preliminary findings suggest that gabexate mesilate could represent a promising therapeutic option for mCRC patients, particularly for those harbouring KRAS, BRAF and PIK3CA mutations, either as mono-therapy or in addition to standard chemotherapy regimens. Further studies to better elucidate gabexate mesilate mechanism of action in CRC cells are therefore warranted.